Mobile Platform: The third-party developers' perspective - Dao, Trang (2013)
Android and iOS is the two leading platforms in the mobile application market. Which platform is the better choice for an app developer to design apps for is not an easy question to answer. Therefore, to help answer this question, I have conducted 17 in-depth interviews with app developers who have made apps for Android or iOS or both platforms, as a way to gain to insight in their perspective. Some developers prefer iOS whereas the others prefer Android and for different reasons. Each platform has its own advantages as well as drawbacks. However, most developers that were interviewed prefer iOS to Android. The research findings indicate that market share is the most important criteria for developers to make their decisions in choosing a particular platform. Besides, usability and device fragmentation are other important factors. The study will also examine how developers can position their apps in the market, what business model they can employ with regards to pricing and how to market their apps and how these factors can also affect their choice on platform. This paper will also examine the issue regarding users’ privacy through the lens of app developers. Finally, I developed a theoretical model illustrating the factors affecting developer’s choice of platform.